Monosymptomatic hypochondriacal psychosis: A case report being used risperidone - Atmaca, Murad; Kulo?lu, Murat; Tezcan, A. Ertan (My University, 2001)
Monosymptomatic hypochondriacal psychosis is a diagnosis that is used to define delusional hypochondriac occupations without another thougtht and behavior abnormalities. Owing to its rarity and being misdiagnosed on differential diagnosis, it was aimed to present and to discuss a case that exhibits interesting clinical presentation. The patient who had some occupations such as feeling odor of detergent, circulating detergent in his blood and its blood reacting with detergent had applied to many medical and paramedical treatment pathways for two and half years ago. Risperidone was started and a significant improvement was observed. The improvement was sustained for follow-up period. It was supported that these cases were frequently neglected by parapsychiatric physicians on differential diagnosis and exposed to many diagnostic and therapeutic approaches. In addition, we suggested that risperidone might be an effective alternative treatment in these cases.
Monosemptomatik hipokondriak psikoz: Risperidon kullanilan bir olgu
Keywords: Delusional disorder; Monosymptomatic hypochondriacal psychosis; Risperidone